Analysis of energy flows and emission characteristics of conventional diesel and isobaric combustion in an optical engine with laser diagnostics. (15th April 2023) - Goyal, Harsh; Panthi, Niraj; AlRamadan, Abdullah S.; Cenker, Emre; Magnotti, Gaetano
Abstract: In this study, the thermodynamic analysis of energy distribution, exhaust emissions, and particulate characterization was conducted in an optical engine with an all-metal configuration. Additionally, the line-of-sight integrated imaging of combustion luminosity, and OH* chemiluminescence along with planar laser induced fluorescence of formaldehyde (HCHO-PLIF), and planar laser induced incandescence of soot (soot-PLII) were applied in the optical configuration. The experiments were conducted with conventional diesel combustion at λ = 3 (i.e., CDC), isobaric combustion at λ = 3 (i.e., Iso3), and isobaric combustion at λ = 4.2 (i.e., Iso4.2) using n-heptane fuel. Compared to Iso3 and CDC, Iso4.2 yielded higher thermal efficiency and lower heat losses; whilst the exhaust losses were exacerbeted. Isobaric combustion also resulted in lower NOx but increased soot emissions. For all operating conditions, the combustion luminosity and OH* chemiluminescence imaging showed that the signal grows and develops from the jet-axis downstream of the nozzle to the jet-wall impingement point, followed by movement towards the squish region. HCHO-PLIF showed that isobaric combustion leads to a faster transition of low-to high-temperature reactions compared to CDC. Soot-PLII showed increased in-cylinder soot distribution for isobaric combustion due to lesser charge pre-mixing time and spray-flame interaction induced by close-coupled injections. Graphical abstract: Image 1 Highlights: Isobaric combustion exhibits higher efficiency, lower heat losses, and reduced NOx compared to CDC. Above 150 nm, the particle number concentration and surface area are lower for isobaric combustion. Combustion luminosity, OH* chemiluminescence, HCHO-PLIF, and soot-PLII were applied. Faster low-to high-temperature reaction transition for isobaric combustion compared to CDC. Initial soot pockets formed downstream of the nozzle gets subsequently oxidized by the OH radicals.